If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -10 + -7) = 15 Reorder the terms: 3(-10 + -7 + x) = 15 Combine like terms: -10 + -7 = -17 3(-17 + x) = 15 (-17 * 3 + x * 3) = 15 (-51 + 3x) = 15 Solving -51 + 3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + 3x = 15 + 51 Combine like terms: -51 + 51 = 0 0 + 3x = 15 + 51 3x = 15 + 51 Combine like terms: 15 + 51 = 66 3x = 66 Divide each side by '3'. x = 22 Simplifying x = 22
| 8=2(x-3)(x-3) | | 8=2(x-3)2 | | 6b^2+35d-6=0 | | -7z+42=70 | | 5f-5=2f+16 | | 0.16(6-x)=27+2x | | 5/2x+3=-6 | | 11n^2+4n+7=6 | | k+10/3=-4 | | (9x+7x^2-12)+(14-6x-2x^2)= | | r=4x+10 | | 8-10x-4x=-20 | | 2k^2+2k-60=0 | | -14x+8=-20 | | -26j=182 | | -4x+4-6x=-96 | | y+469=712 | | 45+24n+3n^2=0 | | n+3n=14-4n | | 132-x=44 | | 4p=p-20 | | d-680=160 | | 12=3x+12 | | n^2-5n-14= | | 3y=12-3 | | 9.2=r+17.43 | | -5w+2+6w=4+17 | | -799=-17y | | -4x^2+10=8x+4 | | 120=3x+12 | | c+71=36 | | (5w+10)*2+(2w)=380 |